The basics of digital privacy simple tools to protect your personal your information and your identity online - Cherry, Denny (Basics, 2014)
The Basics of Digital Privacy teaches you how to protect the privacy of your data and your identity while surfing, searching, and interacting with others in a virtual world. Author Denny Cherry teaches professionals how to keep huge databases secure, and he will introduce you to the basic concepts of protecting your identity, your financial data, and your personal information